Technical and Economical Demands on 25K - 77K Refrigerators for Future HTS - Series Products in Power Engineering - Gromoll, B (Advances in Cryogenic Engineering; Volume 49B, 2004)
For the future high temperature superconductivity, HTS, series products new refrigerators are essential. Demands are made on these which are only partly fulfilled by refrigerators available in the market today. This refers to cooling power, initial cost and in particular reliability. Without proper refrigeration techniques it will be almost impossible to bring HTS products to the market. Based on the experiences made by the construction and operation of HTS prototypes within our company, like the 400 kW motor, 1.2 MVA current limiter and 1 MVA traction-transformer provided with refrigerators which are available in the market today, criteria have been established to identify the future technical and economical requirements. These criteria apply to efficiency, maintainability, operation flexibility, feasibility of integration and performance/cost ratio. For the temperature range of 20 K to 77 K cooling with Gifford-McMahon, Pulse Tube, Stirling and Mixture-Cascade refrigerators are applicable. The development potential of these processes are compared for the different applications in future series products. Presented are the necessary steps towards reliable and economic refrigerators from the viewpoint of an equipment manufacturer. These are essential for a market entry in the year 2008.